2010
DOI: 10.1136/jmg.2010.081216
|View full text |Cite
|
Sign up to set email alerts
|

Germline DICER1 mutations and familial cystic nephroma

Abstract: It has been established that DICER1 mutations cause familial CN and may be implicated in bilateral CN. No germline mutations were found in the patients with WT, suggesting that DICER1 mutations are unlikely to have a major role in the aetiology of sporadic WT. These results provide further evidence implicating miRNA dysregulation in tumourigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 24 publications
2
69
0
1
Order By: Relevance
“…Initial clinical studies found that PPB and PPB-FTDS patients carry heterozygous DICER1 germline mutations and no homozygous loss of DICER1 was observed [6,33], which supported the DICER1 haplo-insufficiency hypothesis. However, this model was contradicted by recent studies showing that Dicer1-null cells (Kras G12D Trp53 −/ − Dicer1 −/ − ) from a mouse sarcoma cell line are competent for tumour formation, and that Pten/Dicer1 double-knockout mice develop primary fallopian tube tumours [17,34].…”
Section: Discussionmentioning
confidence: 84%
“…Initial clinical studies found that PPB and PPB-FTDS patients carry heterozygous DICER1 germline mutations and no homozygous loss of DICER1 was observed [6,33], which supported the DICER1 haplo-insufficiency hypothesis. However, this model was contradicted by recent studies showing that Dicer1-null cells (Kras G12D Trp53 −/ − Dicer1 −/ − ) from a mouse sarcoma cell line are competent for tumour formation, and that Pten/Dicer1 double-knockout mice develop primary fallopian tube tumours [17,34].…”
Section: Discussionmentioning
confidence: 84%
“…Germline DICER1 mutations were first found in patients with renal tumors in 2010, but DICER1 mutations were not identified in the germline of any of 50 patients with sporadic Wilms' tumors (Bahubeshi et al 2010). This shows that although DICER1 mutations were later associated with Wilms' (Foulkes et al 2011;Slade et al 2011), they are not fully penetrant.…”
Section: The Mirna Pathway In Wilms' Tumorigenesismentioning
confidence: 99%
“…The central importance of DICER1 in animal biology is emphasized by studies of Dicer1 knockout mice and of morpholino knockdown Dicer1 zebrafish, which demonstrated that null-Dicer1 embryos are incompatible with life [Bernstein et al, 2003;Wienholds et al, 2003]. Moreover, human heterozygous germline DICER1 mutations have been clearly associated with several rare childhood tumors such as pleuropulmonary blastoma (PPB) (MIM# 601200) Slade et al, 2011], cystic nephroma (CN) [Bahubeshi et al, 2010;Hill et al, 2009;Slade et al, 2011], ovarian sex-cord-stromal tumors, especially Sertoli-Leydig cell tumor (SLCT) [Rio Frio et al, 2011;Schultz et al, 2011;Slade et al, 2011], and multinodular goiter (MNG) [Rio Frio et al, 2011] (MIM# 138800). Deleterious germline DICER1 mutations have also been reported in single individuals with ciliary body medulloepithelioma, medulloblastoma, and Wilms tumor (WT) [Slade et al, 2011].…”
Section: Introductionmentioning
confidence: 98%
“…Most associated conditions occur in children under age 10 years, although ovarian tumors and MNG are described in children and in adults up to approximately 30 years of age. Because these diagnoses, especially when occurring in familial aggregations or with PPB, suggest the presence of a DICER1 mutation, we investigated several suspicious kindred using previously described molecular diagnostic methods [Bahubeshi et al, 2010;Rio Frio et al, 2011]. We report here DICER1 mutations in seven families, establishing an association between DICER1 mutations and uterine cervix embryonal rhabdomyosarcoma (cERMS), cervical primitive neuroectodermal tumor (cPNET), and juvenile intestinal polyps, providing further evidence linking DICER1 mutations to WT, and suggesting that congenital malformations such as pulmonary sequestration (PS) and perhaps transposition of the great arteries (TGA) may be rare phenotypic expressions.…”
Section: Introductionmentioning
confidence: 99%